Hubungan Pengetahuan Ibu Tentang Gizi dan Kartu Menuju Sehat (KMS) dengan Status Gizi Batita di Posyandu Kelurahan Jatimakmur Kota Bekasi Tahun 2021 - Asiah Nada Afifah (2021)
Nutritional problems can reduce the quality of human resources in the future. At the age of toddlers (1-3 years old) is a period that determines the development of the brain. At this age, children have grown and developed vastly and are particularly vulnerable to malnutrition. The test of this research is to know the correlation between mother's knowledge about nutrition and KMS (healthy card) with nutritional status of toddlers (1-3 years) in the Posyandu Jatimakmur, Bekasi, 2021. The study design used was a cross sectional method with a sample of 189 mothers of toddlers (1-3 years). The sampling technique used by this research was cluster random sampling and proportionate random sampling. The results showed that there was no relationship between the mother's age, employment status, maternal education, and family member's with nutritional status. There was a relationship between family income, knowledge about nutrition, knowledge about KMS (healthy card), and food frequency with nutritional status. Expected that mothers be more active in seeking information about nutrition and KMS (healthy card) from various easily accessible sources of information and mothers have a desire to understand more about KMS so that mothers can observe the nutritional status of toddlers and make efforts to prevent growth disorders properly.